The rural-urban divide, intergroup relations, and social identity formation of rural migrant children in a Chinese urban school. Issue 1 (2nd January 2018) - Zhang, Donghui
Abstract: Through ethnographic fieldwork conducted at a Beijing public school, this study aims to investigate how rural migrant children in China negotiate and construct their identity vis-à-vis the school's local children. Building on social identity theory, this study reveals that rural migrant children develop a strong non-local group identity as a response to the Hukou-based social policy and the occupation-based social hierarchies in contemporary China. Such an identity helps migrant children combat a sense of inferiority that is reinforced by their daily interactions with the socially and economically more advantaged urban peers. However, this group-based identity forestalls intergroup contact and prevents the migrant children from successfully integrating into Chinese urban society.